Tata Kelola Badan Usaha Milik Desa (BUMDes) sebagai Penguatan Ekonomi Desa Ngingas Kecamatan Waru Kabupaten Sidoarjo - Putri, Rentaulina; Munari, Munari (Jurnal Etnik: Ekonomi-Teknik, 2023)
Village autonomy government that focuses on the occurrence of development at the village level. Development in the village aims to advance the village based on increasing Pendapatan Asli Desa (PADes). The effort to increase PADes is to establish Badan Usaha Milik Desa (BUMDes) in each village and sub-district. The development of BUMDes in each village and sub-district encourages an increase in village/kelurahan community businesses in managing the village's economic potential. The success of BUMDes depends heavily on how BUMDes is managed so that it can provide benefits to the village/kelurahan. This study aims to analyze the governance of village-owned enterprises (BUMDes) as strengthening the village economy and the contribution of BUMDes to PADes. The method used in this study is descriptive qualitative with data collection using interview techniques, observation and documentation. This research was conducted at the Ngingas Makmur Abadi BUMDes, Ngingas Village, Waru District, Sidoarjo Regency. In this study the data obtained came from the Commissioner of BUMDes, the Director of BUMDes and the people of Ngingas village. The results of this study show that the governance process for the Ngingas Makmur Abadi BUMDes is in accordance with the provisions set by the Ministry of Villages. The implementation of the Ngingas Makmur Abadi BUMDes contributes to Village Original Income from 30% of the distribution of the remaining business results and contributes to strengthening the village economy through employment as community empowerment and supports IKM in Ngingas Village.